29 Geriatric Emergency Medicine (GEM) Bootcamp and Bootcamp Bitesize Training. (6th February 2020) - Sendall, C; Williamson, M; Solomon, C; Belcher, R
Abstract: Introduction: In 2016 we ran a successful pilot of Geriatric Emergency Medicine (GEM) Bootcamp at Imperial College Healthcare Trust. This has developed into an annual regional conference which to date has been attended by over 440 delegates. This year we have been able to expand GEM Bootcamp to offer smaller 'Bitesize Bootcamps' with tailored learning for individual organisations, with more than 100 delegates already having accessed this resource. Methods: In developing the curriculum for GEM Bootcamp and Bootcamp Bitesize we engaged a significant range of local healthcare providers. We undertook a learning needs analysis, which surveyed the target audience- specifically looking for self-reported gaps in knowledge- as well as analysing data from incidents, complaints and compliments. This allowed us to identify areas which there was opportunity for learning as well as ensuring a personalised curriculum Results and conclusions: GEM Bootcamp feedback was overwhelmingly positive, with 100% of delegates stating they would recommend the day to colleagues. The relevance to practice was rated 4.4/5 with many positive comments about the opportunity to meet many interested people, generate conversations and raise awareness of frailty. The self-reported improvement of knowledge was from 2.95/5 pre-course to 3.89/5 post course. To date we have delivered Bitesize Bootcamp to a local nursing care centre (which accounts for 50% of the admissions from care homes to the ICHT), London Ambulance Service (LAS), acute medicine and medicine for the elderly from a local trust, ICHT A&E nurses and Capital Nurse trainees. All bitesize training delegates self-reported an increase in their frailty knowledge. On average over the 5 bitesize sessions delegates reported an improvement from 3/5 pre-training to 4.1/5 post training. The development of links with local partners and the delivery of a consistent message about best practice in frailty have also been valuable outcomes